(untitled) (International Research Journal of MMC, 2024)
Remittances are a crucial component of the global economy and a significant source of income for developing nations. They contribute significantly to the economic growth of recipient countries by providing investment opportunities, boosting consumption and women’s empowerment, and reducing poverty. The objective of this study is to analyze the impact of remittance income on women’s empowerment in Nepal. The research used a descriptive cross-sectional design and collected primary data through a questionnaire. Five-point likert type scaling technique was used to obtain a response to each question. Data were collected by interviewing individuals who receive remittances from banks and cooperatives in Bhimad City Tanahun. Household were randomly selected as samples including 16 from Bhimad Municipality, 8 from Rishing Rural Municipality, 10 from Ghiriing Rural Municipality, and 6 from Myadge Rural Municipality. All the households in the study area receiving remittance income throughout the year 2023 were considered as the population of the study. Descriptive statistics were employed to present the data through mean, t-test, and percentages. The results of the study showed that remittances significantly contributed to women’s financial independence, education, and healthcare access, poverty alleviation, enhancing decision-making power within households, and promoting participation in community development. The consistently high p-value was 17.30 and lowest p-value was 13.30, high and low p-value indicates that there was a strong consensus among respondents regarding the positive impact of remittances on women’s empowerment. The findings have significant implications for researchers, policymakers, and practitioners. It highlights the need the targeted interventions that maximize the positive impact of remittances on women’s empowerment while addressing potential challenges. Overall, the study emphasizes the need to recognize the critical role of remittances in promoting women’s empowerment and the importance of developing effective strategies to harness their potential.